1994
DOI: 10.1364/ao.33.007288
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffraction by arbitrarily oriented ellipsoids: applications in ektacytometry

Abstract: Anomalous diffraction by an arbitrarily oriented ellipsoid with three different axes is derived. From the resulting expression the relationship between the shape of the ellipsoid and the intensity pattern is immediately evident: The axial ratio of the elliptical isointensity curve equals the axial ratio of the elliptical projected area of the ellipsoid. A comparison of anomalous diffraction with calculations performed with the T-matrix method reveals that the anomalous diffraction approximation is highly accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
8

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 17 publications
0
20
0
8
Order By: Relevance
“…RBC deformability of patients estimated by the Ecktacytometer at day0 is a summation of the cellular deformability of both uninfected (uRBCs) and infected ( Pf RBCs) RBCs fractions, with a contribution to the overall values proportional to their respective size31. Since the vast majority of RBCs in malaria patients are uRBCs, the reduction in RBC deformability results mainly from changes in the uRBCs.…”
Section: Resultsmentioning
confidence: 99%
“…RBC deformability of patients estimated by the Ecktacytometer at day0 is a summation of the cellular deformability of both uninfected (uRBCs) and infected ( Pf RBCs) RBCs fractions, with a contribution to the overall values proportional to their respective size31. Since the vast majority of RBCs in malaria patients are uRBCs, the reduction in RBC deformability results mainly from changes in the uRBCs.…”
Section: Resultsmentioning
confidence: 99%
“…Streekstra et al 12 showed that the scattering by an ellipsoid of dimensions a, b, and c along the x, y and z axes, respectively, positioned at angles θ x , θ y , and θ z to the incident light is equal to the scattering by an ellipsoid characterized by dimensions a', b' and c' along the x', y', and z', respectively ( Figure 1). The orientation dependent dimensions a', b' and c' were calculated as functions of length a (b=a), width c, and orientation angles θ x and θ z as described in 12 . The coordinate transformation was done such as z' would align with the direction of the incident beam Io (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Anomalous diffraction approximation of van de Hulst 13 was used to predict the absorption and scattering from oriented ellipsoidal erythrocytes. The high accuracy of anomalous diffraction for predicting erythrocyte angle dependent scattering has been previously shown 12 . These results can be imported in the numerical models as empirical orientation constants, thereby, reducing their complexity.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These expressions reproduce accurately the extinction efficiency factor for randomly oriented spheroids, although these need not be good at a particular orientation. Scattering by ellipsoids in the ADA has been studied, among others, by Lind andGreenberg (1966), Latimer (1980), Sid'ko (1988), Paramonov (1994), Paramonov et al (1986), Streekstra et al (1994) and Streekstra (1994). A general bridging technique has been developed by Zhao and Hu (2003) to calculate the extinction efficiency factors for particles with various shapes and sizes.…”
Section: Nonspherical Scatterersmentioning
confidence: 99%